Relation between serum vitamin B12 level and duration of treatment with carbamazepine in epilepsy patients (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Vitamin B12 levels in the serum of 58 epileptic patients receiving only carbamazepine for at least 6 months were measured. Same number of epilepsy patients with no history of taking antiepileptic medicine were taken as control. The mean level of vitamin B12 in carbamazepine-treated epileptic patients was 265.5 pg/mL whereas it was 478.3 pg/mL in control. Increased duration of treatment of carbamazepine in epilepsy caused significantly decreased level of serum vitamin B12 (Pearson correlation coefficient, r = -0.9, p